Advanced paternal age directly impacts mouse embryonic placental imprinting. - Michelle M Denomme; Jason C Parks; Blair R McCallie; Nathan I McCubbin; William B Schoolcraft; Mandy G Katz-Jaffe (PLoS ONE, 2020)
The placental epigenome plays a critical role in regulating mammalian growth and development. Alterations to placental methylation, often observed at imprinted genes, can lead to adverse pregnancy complications such as intrauterine growth restriction and preterm birth. Similar associations have been observed in offspring derived from advanced paternal age fathers. As parental age at time of conception continues to rise, the impact of advanced paternal age on these reproductive outcomes is a growing concern, but limited information is available on the molecular mechanisms affected in utero. This longitudinal murine research study thus investigated the impact of paternal aging on genomic imprinting in viable F1 embryonic portions of the placentas derived from the same paternal males when they were young (4-6 months) and when they aged (11-15 months). The use of a controlled outbred mouse model enabled analysis of offspring throughout the natural lifetime of the same paternal males and excluded confounding factors like female age or infertility. Firstly, paternal age significantly impacted embryonic placental weight, fetal weight and length. Targeted bisulfite sequencing was utilized to examine imprinted methylation at the Kcnq1ot1 imprinting control region, with significant hypermethylation observed upon natural paternal aging. Quantitative real-time PCR assessed imprinted gene expression levels at various imprinting clusters, resulting in transcript level alterations attributable to advanced paternal age. In summary, our results demonstrate a paternal age effect with dysregulation at numerous imprinted loci, providing a mechanism for future adverse placental and offspring health conditions.